Community-Based Islamic Education for Women’s Empowerment in Coastal Areas: The Role of Religious Traditions and Microfinance - Wigati, Sri; Afandi, Agus; Fauziah, Nailatin; Yudha, Ana Toni Roby Candra (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
This study strengthens the economic capabilities education of women in fishing communities, particularly during droughts caused by the west wind season. It leverages local religious traditions and the silaturrahim guardian boarding school students' forums for empowerment. Using a qualitative-phenomenological approach, the research immerses in fisherwomen’s daily lives. The findings include: (1) Community engagement and savings-loan groups help women identify challenges and recognize their potential. (2) The empowerment process fosters collaborative problem-solving, enabling women to act naturally based on their capabilities. (3) Organizational and financial management training improves family economic outcomes. However, the approach's effectiveness is tied to the community’s cultural and religious context, requiring continuous support from empowerment teams and forums. The study’s originality lies in integrating religious traditions with economic initiatives, utilizing silaturrahim forums to empower women in fishing communities. This method not only addresses immediate financial needs but also establishes a sustainable, community-driven model for long-term economic resilience and self-sufficiency. Tujuan penelitian ini untuk memperkuat edukasi kemampuan ekonomi perempuan di komunitas nelayan, terutama selama musim kemarau yang disebabkan oleh musim angin barat. Penelitian ini memanfaatkan tradisi keagamaan lokal dan forum silaturrahim wali santri untuk pemberdayaan. Dengan menggunakan pendekatan kualitatif-fenomenologis, penelitian ini menyelami kehidupan sehari-hari perempuan nelayan. Temuan-temuannya meliputi: (1) Keterlibatan masyarakat dan kelompok simpan pinjam membantu perempuan mengidentifikasi tantangan dan mengenali potensi mereka. (2) Proses pemberdayaan mendorong pemecahan masalah secara kolaboratif, sehingga memungkinkan perempuan untuk bertindak secara alami berdasarkan kemampuan mereka. (3) Pelatihan manajemen organisasi dan keuangan meningkatkan hasil ekonomi keluarga. Namun, efektivitas pendekatan ini terkait dengan konteks budaya dan agama masyarakat, sehingga membutuhkan dukungan berkelanjutan dari tim dan forum pemberdayaan. Keaslian penelitian ini terletak pada pengintegrasian tradisi agama dengan inisiatif ekonomi, dengan memanfaatkan forum silaturahmi untuk memberdayakan perempuan dalam komunitas nelayan. Metode ini tidak hanya memenuhi kebutuhan finansial yang mendesak, tetapi juga membangun model yang berkelanjutan dan digerakkan oleh masyarakat untuk ketahanan dan kemandirian ekonomi jangka panjang.